ANALISIS KRITIS PERAN DALIHAN NATOLU DALAM PERKAWINAN MASYARAKAT BATAK ANGKOLA TAPANULI SELATAN - Risalan Basri Harahap (Jurnal AL-MAQASID: Jurnal Ilmu Kesyariahan dan Keperdataan, 2019)
The marriage law of the Batak Anagkola community of South Tapanuli regulates the role of Dalihan Natolu. The role of Dalihan Natolu is something that cannot be separated in the social life within the Batak Anagkola indigenous community of South Tapanuli. In a legitimate marriage, Dalihan Natolu has outlined and stipulated detailed rules and regulations regarding various social relations between husband and wife, between parents and siblings from each bride, as well as with boru and hula hula from each of them. -either party. The issues to be discussed in this paper are about the application of the Dalihan Natolu principle in the traditional Anagkola Tapanuli Batak customary law, as well as the role of Dalihan Natolu in the process of resolving the marital problems of the Anagkola Batak people in South Tapanuli. In the life of the Anagkola South Tapanuli Batak indigenous people, the Dalihan Natolu principle is very concerned with the collaboration between the roles of the Dalihan Natolu elements themselves, namely dongan tubu, hula-hula, and boru. This is also inseparable from Dalihan Natolu's proverb which says somba marhula-hula, manat mardongan tubu, and elek marboru because it contains a meaning that is profound and must be done if you want to prosper your life. In the Anagkola South Tapanuli Batak indigenous people, the customary leader in the Anagkola South Tapanuli Batak Indigenous community association or organization which adheres to the Dalihan Natolu principle can be said to be a mediator in resolving a marital problem, because the adat leader becomes the party involved between parties the conflict to then resolve the problem between the two troubled parties, where the peaceful solution is prioritized so that it does not drag on problems that result in a divorce.